Management of Teacher Pedagogic Competency Development in Vocational High Schools - Hafidzah, Zulfa; Sumardjoko, Bambang; Maksum, Muh. Nur Rochim (Journal of English Language and Education, 2025)
The quality of education in Vocational High Schools (SMK) is strongly influenced by teachers’ pedagogical competence, especially in the industry 4.0 era which requires continuous competence development through systematic human resource management. This study aims to analyze the management of pedagogical competence development of teachers at SMK Muhammadiyah Pondok Pesantren Imam Syuhodo, covering the stages of planning, implementation, and evaluation. Using a qualitative phenomenological approach and descriptive analytical method, data were collected through interviews, observations, and documentation involving principals, management teams, and teachers. Data validity was tested through source and technique triangulation, and analysis used the Miles Huberman model. The results show that pedagogical competence development is managed through: (1) planning based on supervision, self-evaluation, and student feedback aligned with the school’s vision; (2) implementation via In House Training, workshops, MGMP, lesson study, mentoring, and industry internships supported by the principal’s role as supervisor and motivator; and (3) evaluation through classroom supervision, performance assessment, peer observation, and feedback from students, alumni, and industry. Success is supported by strong management, collaborative professional learning communities, and program relevance to business and industrial needs. The study concludes that systematic and continuous human resource management effectively enhances teachers’ pedagogical quality, integrates Islamic values in learning, and produces competent, Islamic-charactered graduates, serving as a model for other vocational schools.